JUSTICE AND EMPOWERMENT IN THE CLASSROOM:THE SOCIAL EXCHANGE PERSPECTIVE - Mottey, Rejoice (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The study investigated the relationship between students perceptions of justice and empowerment in the Ghanaian classroom. Three hundred and sixty five senior secondary and technical school students purposively and conveniently sampled, completed questionnaires on classroom justice scales comprising; distributive, interactional and procedural justice scales. Correlation analyses indicated a significant positive relationship between classroom justice and student empowerment. Regression analyses revealed procedural justice perceptions as the only predictor of student empowerment . Results are discussed within the framework of the social exchange theory.